Bipolar Disorder and Wilson’s Disease: A Case Report - Bhagat, S; Nepal, H; Verma, A K (Journal of Psychiatrists’ Association of Nepal, 2015)
Wilson’s disease is an uncommon inherited disorder characterized by low serum ceruloplasmin levels, hypercupriuria and Kayser-Fleischer rings. Here we describe the case of a young boy who presented with symptoms of bipolar depression along with bilateral hand tremors. He was started with Quetiapine but symptoms did not improve. Investigations revealed cirrhotic changes of liver, low serum ceruloplasmin levels, presence of Kayser-Fleischer rings. The diagnosis of Wilson’s disease was confirmed by high 24hr. urinary copper levels. Bipolar symptoms improved after 7 months of initiation of oral penicillamine treatment. J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 50-52 DOI: http://dx.doi.org/10.3126/jpan.v3i2.12399